2003
DOI: 10.1093/jac/dkg052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of resistance to ampicillin, gentamicin and vancomycin in Enterococcus faecalis and Enterococcus faecium isolates from clinical specimens and use of antimicrobials in five Nordic hospitals

Abstract: We determined the species distribution and prevalence of ampicillin resistance, high-level gentamicin resistance (HLGR) and vancomycin resistance among clinical enterococcal isolates from five Nordic laboratories (Bergen, Tromsø, Uppsala, Aarhus and Reykjavik). Isolates represented three different groups: (i) all blood culture isolates from 1999; (ii) consecutive in-patient isolates (maximum 40); and (iii) consecutive outpatient isolates (maximum 40) collected during March to May 2000. Antimicrobial use data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
46
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 32 publications
10
46
0
7
Order By: Relevance
“…Most (90.4 %) of our clinical isolates were resistant to at least three of the antibiotics tested, and antibiotic resistance was more common among E. faecium isolates than E. faecalis, which is in agreement with previous studies (Simonsen et al, 2003;Top et al, 2007). For example, ampicillin resistance was detected in 31.4 % of the isolated enterococci, but nearly 93 % of these were E. faecium (P,0.001).…”
supporting
confidence: 91%
“…Most (90.4 %) of our clinical isolates were resistant to at least three of the antibiotics tested, and antibiotic resistance was more common among E. faecium isolates than E. faecalis, which is in agreement with previous studies (Simonsen et al, 2003;Top et al, 2007). For example, ampicillin resistance was detected in 31.4 % of the isolated enterococci, but nearly 93 % of these were E. faecium (P,0.001).…”
supporting
confidence: 91%
“…faecium ratio in hospital infections was reported in three longitudinal microbiologybased studies (10,22,34). In Europe, several reports on the increase in invasive AREF have been published (4,29,33), but to our knowledge ours is the first nationwide study in Europe on the molecular epidemiology of AREF. The emergence of CC17 AREF, resulting in changing E. faecalis/E.…”
Section: Vol 46 2008 Emergence Of Cc17 E Faecium 217mentioning
confidence: 65%
“…This was similar to a study in India where they showed 89.43% isolates resistant to pencillin. 3 However in a cross sectional study Simonsen et al 19 stated E. faecalis isolates were uniformly susceptible to ampicillin, and also only 40% of E. faecium isolates were resistant to ampicillin. Because penicillin is the main stay of therapy for infections due to enterococci, the organism's development of high level resistance to this drug would have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%